PENGARUH PROPORSI PUREE DAGING BUAH PALA DAN BUAH NAGA TERHADAP SIFAT FISIK DAN ORGANOLEPTIK VELVA - Sipahelut, Sophia G. (Jurnal Sains dan Teknologi Pangan, 2023)
ABSTRACT Nutmeg (Myristica fragrans Houtt.) is very abundant in Indonesia, including Maluku. However, the parts of the nutmeg fruit that have high economic value are the nutmeg seeds and mace, while the nutmeg fruit flesh is rarely used, and even ends as waste. One effort to diversify processed nutmeg fruit flesh products is to process them into velva products. The obstacle faced in processing nutmeg fruit flesh is the high tannin content which causes an astringent and bitter taste; thus, it needs to be combined with other fruits, one of which is dragon fruit. The purpose of this study was to determine the best ratio of nutmeg pulp puree and dragon fruit puree based on the physical and sensory properties of velva. The research design used was a one-factor completely randomized design. The parameter was the ratio of nutmeg puree and dragon fruit puree which consisted of four treatments, namely: 90%:10%, 80%:20%, 70%:30%, and 60%:40%. Variables observed were physical characteristics (overrun and melting speed) and organoleptic assessments (taste, aroma, color, texture, and overall acceptance). The results show that the sample that had the highest panelist preference value was found in velva with a 60%:40% ratio of nutmeg puree and dragon fruit puree. The sensory assessments show that the sample had a slight nutmeg taste, pink color, slightly nutmeg aroma, and soft texture. Meanwhile, the physical characteristics show that it had. 12.48% overrun, 11.00 minutes melting speed, and 3.42 pH. Keywords: nutmeg fruit flesh puree, dragon fruit puree, velva ABSTRAK Potensi pala (Myristica fragrans Houtt.) di Indonesia termasuk Maluku sangat melimpah. Namun, bagian buah pala yang memiliki nilai ekonomi tinggi adalah biji dan fuli pala, sedangkan daging buah pala jarang dimanfaatkan, bahkan dibuang begitu saja. Salah satu upaya diversifikasi produk olahan daging buah pala adalah mengolahnya menjadi produk velva. Kendala yang dihadapi dalam pengolahan daging buah pala adalah kandungan tanin yang tinggi yang menyebabkan rasa sepat dan getir, sehingga perlu dikombinasikan dengan buah lain, salah satunya buah naga. Tujuan dari penelitian ini adalah untuk menentukan rasio puree daging buah pala dan puree buah naga yang terbaik berdasarkan sifat fisik dan sensori velva. Rancangan penelitian yang digunakan adalah Rancangan Acak Lengkap satu faktor, yaitu perbandingan puree daging buah pala dan puree buah naga yang terdiri dari empat taraf perlakuan yaitu: 90%:10%, 80%:20%, 70%:30% dan 60%:40%. Parameter yang diamati meliputi uji fisik meliputi overrun dan kecepatan leleh, serta uji sensori meliputi rasa, aroma, warna, tekstur, dan penerimaan keseluruhan. Hasil penelitian menunjukkan bahwa sampel yang memiliki nilai kesukaan panelis tertinggi terdapat pada velva dengan perbandingan puree daging buah pala dan puree buah naga 60%:40% dengan karakteristik sensori agak berasa pala, berwarna merah muda, agak beraroma pala, bertekstur lembut dan karakteristik fisik overrun 12,48%, kecepatan leleh 11,00 menit, dan pH 3,42. Kata kunci : puree daging buah pala, puree buah naga, velva